Rumors in the Workplace Affecting Organizational Change Readiness (Global Journal of Management and Business Research, 2014)
The spread of Rumors/Grapevines/Rumor-mills continues to be an issue for most midlarge organizations throughout the United States. Rumors have been an integral part of American political views and have had an effect on most organizational change initiatives. The notion of not knowing something provokes human instincts to seek the truth among employees by spreading rumors. In so doing, rumor-mills have the potential to penetrate most organizational structures, which could lead to organizational change derailment if not addressed accordingly.
Keywords: public administration; public service; management; leadership organizational development; learning organizations; organizational learning; organizatio